Carbon dots: Discovery, structure, fluorescent properties, and applications - El-Shafey Asmaa M. (De Gruyter, 2021)
Nanotechnology has become one of the most important topics since the beginning of the twenty-first century in numerous fields including drug synthesis and delivery, environmental protection, electronics manufacture, and astronomy due to their nanoscale particles and their properties. The traditional semi-quantum dots are replaced by a new category of fluorescent carbon nanomaterials. Carbon dots (CDs) have been explored in the last few years for their simple synthetic accession, good bio-consonance, and several revelation applications. This review explains the fluorescent properties of CDs in brief, giving also a background on CDs discovery, structure, and composition, as well as on nanocomposites, green synthesis, and their applications. Resources conservation can be achieved by using recycled substances for sustainable development which lead to a new technology. Fluorescent CDs synthesized from food wastes like bananas, orange peel waste, sugarcane bagasse, Trapa bispinosa peels, bread, and jaggery have several applications such as sensing, drug delivery, gene transfer, biological imaging, and food safety. In this study, we concentrate on CDs greener methods to prepare effective and biocompatible CDs.